2016
DOI: 10.1016/j.jnucmat.2016.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Investigating microstructural evolution during the electroreduction of UO2 to U in LiCl-KCl eutectic using focused ion beam tomography

Abstract: Investigating microstructural evolution during the electroreduction of UO 2 to U in LiCl-KCl eutectic using focused ion beam tomography,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…This is indicative of the chemical reaction proceeding to completion. The intensity of the diffraction peaks of U is seen to decrease slightly at $ 900 s and is most likely due to small amounts of powder falling out of the MCE due to the volume change associated with the reduction process (Brown et al, 2016). In the context of pyroprocessing, this oxide reduction process could potentially be performed inside the electrorefiner unit, negating the use of the direct oxide reduction unit.…”
Section: Resultsmentioning
confidence: 99%
“…This is indicative of the chemical reaction proceeding to completion. The intensity of the diffraction peaks of U is seen to decrease slightly at $ 900 s and is most likely due to small amounts of powder falling out of the MCE due to the volume change associated with the reduction process (Brown et al, 2016). In the context of pyroprocessing, this oxide reduction process could potentially be performed inside the electrorefiner unit, negating the use of the direct oxide reduction unit.…”
Section: Resultsmentioning
confidence: 99%
“…The diusional tortuosity obtained from molecular diusion simulation or random walk simulation was also used to substitute the hydraulic tortuosity in hydraulic conductivity studies of porous rocks (Nakashima and Kamiya, 2007;Masís-Meléndez et al, 2014;Peng et al, 2014;Backeberg et al, 2017). Numerical simulation of thermal conduction was adopted to evaluate the diusional tortuosity of porous media (Cooper et al, 2013;Tjaden et al, 2016;Brown et al, 2016;Sun et al, 2016). Besides, the geometrical tortuosity is commonly used as an alternative to physical tortuosities to model transport properties of porous media (Montes et al, 2007;Sun et al, 2011;Cecen et al, 2012;Holzer et al, 2013;Berg, 2014;Kaczmarek et al, 2017;Li et al, 2017), such as permeability, eective diusivity, formation resistivity factor and thermal conductivity.…”
Section: Physical Simulationmentioning
confidence: 99%
“…calcium titanate) due to the salt cation reacting with the oxygen ions on the surface. Moreover, Brown et al [19] showed significant changes in the tortuosity of the cathode microstructure during electrochemical reduction of UO2 to U in molten LiCl-KCl eutectic which could also impede the transport of oxygen anions.…”
Section: Challenges For Electrochemical Reduction In Molten Saltsmentioning
confidence: 99%